Does your job really matter? Job-specific cancer incidence among a cohort coal mine workers in Queensland, Australia - Deborah Catherine Glass; Stella May Gwini; Anthony Del Monaco; Lin Fritschi; Michael J. Abramson; Malcolm Ross Sim; Karen Walker-Bone (International Archives of Occupational and Environmental Health, 2026)
Purpose Globally, coal production exposes millions of workers to coal mine dust. This study aimed to measure overall and site specific cancer incidence among coal mine workers (CMW) who performed different types of work. Methods A retrospective cohort of CMW in Queensland, Australia, was assembled using health assessment records from 1992. CMW were grouped by job type and then into Work Categories and linked to the Australian Cancer Database up to 2016. Standardized cancer incidence ratios (SIR) and relative cancer incidence ratios (aRIR) within the cohort, adjusted for age, era, and smoking status, were calculated for men and women with Poisson regression. Results There were 5,568 cancers diagnosed among 146,553 men and 396 in 19,927 women. The overall cancer risk was comparable to that of the general population for most Work Categories. The risk of lung cancer was higher for male Production (SIR 123, 95% Confidence Interval [CI] 107–142; adjusted Relative incidence Ratio (aRIR) (adjusted for era, age and smoking status) 1.23, 95%CI 0.99-1.52) and Construction workers (SIR 189, 95%CI 31–272; aRIR 1.78, 95%CI 1.20–2.62) when compared with the Australian population and within the cohort after adjusting for smoking. Laryngeal cancer was increased in Production workers (SIR 145, 95%CI 100–212). Conclusions Increased rates of lung and laryngeal cancers were identified for male Production workers and lung cancer for Construction workers. These could be related to mine workplace exposures such as silica and diesel engine exhaust.

Non-respiratory health risks and mortality associated with fighting bushfires (wildfires): a systematic review - Asmare Gelaw; Win Wah; Deborah C. Glass; Malcolm R. Sim; Ryan Hoy; Janneke Berecki-Gisolf; Karen Walker-Bone (International Archives of Occupational and Environmental Health, 2025)
Background Bushfires (also known as wildland or forest fires) expose emergency responders to occupational hazards under exceptional circumstances. Whilst the health impacts of structural firefighting have been studied, less is known about the non-respiratory health impacts or risk of mortality amongst bush firefighters, who can be volunteers. More information about health risks is needed to generate effective prevention strategies. Objective To critically evaluate and synthesise the published evidence about the non-respiratory health risks and risk of mortality associated with bushfire fighting. Methods A systematic literature search was conducted in Medline, Scopus, and Embase to identify studies evaluating morbidity or mortality or associated risk factors among bushfire fighters. The quality of included studies was evaluated twice independently using a specific quality assessment tool. Results Twenty-seven studies were included. 11(41%) were assessed as moderate quality and 16(59%) as low quality. There is a growing body of evidence for adverse short-term impacts of bushfire fighting on mental health and injuries. Linkage studies showed that volunteer firefighters had lower mortality and cancer risk in their late forties compared to the general population. Conclusion Most studies relied on cross-sectional and retrospective designs without comparison groups, limiting the ability to draw robust conclusions. It is essential to conduct higher-quality research using prospective designs and longer-term follow-up to better understand the health outcomes of bushfire fighting, particularly given the anticipated increase in the frequency and severity of bushfires.

Anomalous temperatures increase occupational injuries, illnesses and associated cost burden in Australia - Matthew A. Borg; Jianjun Xiang; Olga Anikeeva; Bertram Ostendorf; Blesson Varghese; Keith Dear; Dino Pisaniello; Alana Hansen; Kerstin Zander; Malcolm R. Sim; Peng Bi (Urban Climate, 2025)

Systematic review of impacts of occupational exposure to wildfire smoke on respiratory function, symptoms, measures and diseases - Win Wah; Asmare Gelaw; Deborah C. Glass; Malcolm R. Sim; Ryan F. Hoy; Janneke Berecki-Gisolf; Karen Walker-Bone (International Journal of Hygiene and Environmental Health, 2025)

Impact of extreme bushfire seasons on rates of occupational injury and disease compensation claims in first responders - Win Wah; Janneke Berecki-Gisolf; Deborah C. Glass; Ryan F. Hoy; Malcolm R. Sim; Alex Collie; Karen Walker-Bone (International Archives of Occupational and Environmental Health, 2024)

Current and projected heatwave-attributable occupational injuries, illnesses, and associated economic burden in Australia - Matthew A. Borg; Jianjun Xiang; Olga Anikeeva; Bertram Ostendorf; Blesson Varghese; Keith Dear; Dino Pisaniello; Alana Hansen; Kerstin Zander; Malcolm R. Sim; Peng Bi (Environmental Research, 2023)

Long-term impact of the 2014 Hazelwood coal mine fire on emergency department presentations in Australia - Catherine L. Smith; Caroline X. Gao; Rongbin Xu; Jillian F. Ikin; Christina Dimitriadis; Matthew TC. Carroll; Malcolm R. Sim; Dion Stub; Tyler J. Lane; Michael J. Abramson; Yuming Guo (Environmental Research, 2023)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Gender differences in respiratory health outcomes among farming cohorts around the globe: findings from the AGRICOH consortium - Jonathan Fix; Isabella Annesi-Maesano; Isabelle Baldi; Mathilde Boulanger; Soo Cheng; Sandra Cortes; Jean- Charles Dalphin; Mohamed Aqiel Dalvie; Bruno Degano; Jeroen Douwes; Wijnand Eduard; Grethe Elholm; et al. (Journal of Agromedicine, 2021)

The impact of sustained hot weather on risk of acute work-related injury in Melbourne, Australia - Judith Anne McInnes; Ewan M. MacFarlane; Malcolm R. Sim; Peter Smith (International Journal of Biometeorology, 2018)

Endotoxin exposure and lung cancer risk: a systematic review and meta-analysis of the published literature on agriculture and cotton textile workers - Virissa Lenters; Ioannis Basinas; Laura Beane-Freeman; Paolo Boffetta; Harvey Checkoway; David Coggon; Lützen Portengen; Malcolm Sim; Inge M. Wouters; Dick Heederik; Roel Vermeulen (Cancer Causes & Control, 2010)

Relationship between cardiopulmonary mortality and cancer risk and quantitative exposure to polycyclic aromatic hydrocarbons, fluorides, and dust in two prebake aluminum smelters - Melissa C. Friesen; Geza Benke; Anthony Del Monaco; Martine Dennekamp; Lin Fritschi; Nick de Klerk; Jan L. Hoving; Ewan MacFarlane; Malcolm R. Sim (Cancer Causes & Control, 2009)

Occupational exposure to ionizing and non-ionizing radiation and risk of non-Hodgkin lymphoma - Ken K. Karipidis; Geza Benke; Malcolm R. Sim; Timo Kauppinen; Anne Kricker; Ann Maree Hughes; Andrew E. Grulich; Claire M. Vajdic; John Kaldor; Bruce Armstrong; Lin Fritschi (International Archives of Occupational and Environmental Health, 2007)

Occupational exposure to low frequency magnetic fields and the risk of low grade and high grade glioma - Ken Kyriakos Karipidis; Geza Benke; Malcolm R. Sim; Michael Yost; Graham Giles (Cancer Causes & Control, 2007)

An Ecological Study of Organochlorine Pesticides and Breast Cancer in Rural Victoria, Australia - Narges Khanjani; Dallas R. English; Malcolm R. Sim (Archives of Environmental Contamination and Toxicology, 2006)

Exposure to Inorganic Arsenic in Soil Increases Urinary Inorganic Arsenic Concentrations of Residents Living in Old Mining Areas - Andrea L. Hinwood; Malcolm R. Sim; Damien Jolley; Nick de Klerk; Elisa B. Bastone; Jim Gerostamoulos; Olaf H. Drummer (Environmental Geochemistry and Health, 2004)

Respiratory symptoms and lung-function changes with exposure to five substances in aluminium smelters - Lin Fritschi; Malcolm R. Sim; Andrew Forbes; Michael J. Abramson; Geza Benke; William A. Musk; Nicholas H. de Klerk (International Archives of Occupational and Environmental Health, 2003)

Respiratory symptoms and lung function in bauxite miners - Jeremy R. Beach; Nicholas H. de Klerk; Lin Fritschi; Malcolm R. Sim; A. William Musk; Geza Benke; Michael J. Abramson; John J. McNeil (International Archives of Occupational and Environmental Health, 2001)

Regulation of desmosomal cell adhesion in human tumour cells by polyunsaturated fatty acids - Wen G. Jiang; Sim K. Singhrao; Stephen Hiscox; Maurice B. Hallett; Richard P. Bryce; David F. Horrobin; Malcolm C. A. Puntis; Robert E. Mansel (Clinical & Experimental Metastasis, 1997)